A comprehensive review on various non-isolated power converter topologies for a light-emitting diode driver - Vishnuram, Pradeep; Narayanamoorthi, R.; Vijayakumar, K.; Bajaj, Mohit; Shouran, Mokhtar; Abdul Samad, Bdereddin; Kamel, Salah (Frontiers in Energy Research, 2022)
Light Emitting Diode (LED) lighting applications aided by power electronic control have become very attractive in recent past. For LED lighting applications, it is essential to design a converter with single/multi output for handling multiple loads. As the LED load is more sensitive to the change in input/converter parameters, it is necessary to regulate the current with respect to the design specifications. In this paper, several LED topologies are reviewed with the focus on power density, single/multi load operation, size and reliability. Several converter topologies are reviewed and compared in terms of power rating, number of semiconductor switches, isolation and efficiency. Various modulation techniques used for dimming control is briefed. The salient features of each converter topology is discussed with the power rating and application for which the topology can be preferred. So the selection of the power factor correction (PFC) and low source side harmonics converter topology are presented. This paper will be useful for the kindly researchers who are working in the development of LED driver.